Republic of Cabo Verde Public Expenditure Review : Revisiting the Efficiency of Public Spending to Reduce Debt and Improve Education and Health Outcomes - World Bank (World Bank, Washington, DC, 2019)
This Public Expenditure Review (PER) was prepared by the World Bank at the request of the Ministry of Finance of Cabo Verde. With a debt-to-GDP ratio of 126 percent in 2017, Cabo Verde is the most indebted country in Sub-Saharan Africa. The country is also at a high of risk of external debt distress. As part of fiscal consolidation efforts to reduce debt, this PER identifies measures to boost fiscal revenues and improve the efficiency of public spending with emphasis on health and education. The report recommends tax policy measures to stem revenue loss from ineffective tax expenditures while strengthening revenue administration and tax compliance. There is space to reduce spending inefficiencies on goods and services, wages and salaries yielding potential fiscal savings. Investment in human capital is prioritized in Cabo Verde but there is scope to improve efficiency and outcomes. In education, reducing repetition rates and addressing human resources issues are key to avoiding waste and improving outcomes. In health, the report recommends measures to improve the allocation of resources to health units. If implemented, these measures could result in combined fiscal savings of at least 2.5 percent of GDP. Finally, continued rationalization of central government fiscal support to State-Owned Enterprises (SOEs) is required to support a gradual reduction of the debt-to-GDP ratio over the medium term. The report includes five chapters. Chapter one discusses the key drivers of fiscal balances and public debt in Cabo Verde and explores different options to put debt on a downward trajectory. Chapters two and three analyzes in detail the respective performances of fiscal revenues and spending over 2010 to 2017. Chapters four and five reviews public spending in the health and education sectors with emphasis on efficiency. Equity issues as also covered in chapters four and five.